STRATEGI PROMOSI DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA KE CANDI PRAMBANAN JOGYAKARTA - Erna Wigati (Riset Manajemen dan Akuntansi, 2018)
This study aims to determine the strategies carried out by the managers of Prambanan Temple in increasing foreign tourist visits, the obstacles faced in increasing foreign tourist visits to visit Prambanan temple, and how to overcome the obstacles faced in increasing foreign tourist visits to the Prambanan Temple. The method used in this study was the observation method by the researchers directly observing Prambanan Temple in Yogyakarta and direct interviews with Prambanan Temple Managers both at the unit branch and at the center. The method used in this study is the theory of triangulation methods, namely from the data sources researchers draw conclusions. Data analysis of this study uses an interactive analysis model consisting of three activities that occur simultaneously, namely data reduction, data presentation and conclusion or verification. The results of this study are promotional strategies carried out by Prambanan Temple Managers in increasing foreign tourist visits by conducting promotional and sales activities in collaboration with related stakeholders including Travel Agents, Ministry of Tourism, Indonesian Embassy, VITO, Managers of the overseas world heritage, through exhibitions, Sales Mission, table top and invite Family Trip for overseas tourism actors. Constraints faced by Prambanan Temple managers in increasing visits by foreign tourists to visit Prambanan temple are: a). Accessibility / Direct Flights from abroad to Jogja are still very limited which results in less competitive tour packages in Jogja, especially for visiting Prambanan Temple, b) competition with world heritage abroad, c). The occurrence of various natural disasters and security issues which resulted in a travel warning from potential countries of the foreign tourist market. How to overcome the obstacles faced by managers in increasing foreign tourist visits to visit Prambanan temple are: a). Increasing promotional activities in collaboration with relevant stakeholders to the Existing and Newmarket. b) improve the quality of services in tourism objects and improve access to information about products and services. c). Cooperate with distribution channels and online travel agents in destination ticket sales. d). Development of products and facilities that are in line with the concept of preservation of cultural heritage. The conclusion of this research is that the promotion strategies carried out by foreign managers both in units or centers have been carried out as much as possible and in various ways such as through exhibitions, Sales Missions, table top and inviting Family Trips to foreign tourists. And suggestions from this study required a lot of understanding human resources in IT to support promotional activities in the coming year. Keywords: strategy, promotion, tourist, foreign countries, prambanan temple